Kalanchoe blossfeldiana cultivation on different substrates containing yerba mate residues (Research, Society and Development, 2021)
In search of a low environmental impact agriculture, the objective of this work was to evaluate the cultivation of Kalanchoe blossfeldiana Poelln. (calandiva) cultivate Amora, submitted to different substrates containing yerba mate residues in its composition. The experiment was carried out in a completely randomized design, with five treatments composed by the different mixtures of the commercial substrate and the composted yerba mate residue, obtaining the compositions: S1: 100% commercial substrate (SC); S2: 50% SC + 50% yerba mate residue (REM); S3: 25% SC + 75% REM; S4: 75% SC + 25% REM and S5: 100% REM, with five replications, each experimental unit consisted of a plant pot. The variables were analyzed in terms of plant height and root length, inflorescence diameter, number of flowers and leaves and fresh root mass. It was observed that the development of calandiva plants was similar with the different combinations containing the commercial substrate and the residue of yerba mate. However, the substrate containing only the residues of yerba mate is not recommended for this cultivation. Finally, it is recommended for the cultivation of calandiva in pots the use of the substrate composed of 50% commercial substrate + 50% yerba mate residue (S2).